Asymmetric Synthesis of Adjacent Tri‐ and Tetrasubstituted Carbon Stereocenters: Organocatalytic Aldol Reaction of an Hydantoin Surrogate with Azaarene 2‐Carbaldehydes. Issue 53 (3rd September 2019) - Izquierdo, June; Demurget, Noémie; Landa, Aitor; Brinck, Tore; Mercero, Jose M.; Dinér, Peter; Oiarbide, Mikel; Palomo, Claudio
Abstract: A bifunctional amine/squaramide catalyst promoted direct aldol addition of an hydantoin surrogate to pyridine 2‐carbaldehyde N ‐oxides to afford adducts bearing two vicinal tertiary/quaternary carbons in high diastereo‐ and enantioselectivity (d.r. up to >20:1; ee up to 98 %) is reported. Acid hydrolysis of adducts followed by reduction of the N ‐oxide group yields enantiopure carbinol‐tethered quaternary hydantoin‐azaarene conjugates with densely functionalized skeletons. DFT studies of the potential energy surface (B3LYP/6–31+G(d)+CPCM (dichloromethane)) of the reaction correlate the activity of different catalysts and support an intramolecular hydrogen‐bond‐assisted activation of the squaramide moiety in the transition state of the catalytic reaction. Abstract : Assembled by aldol : A highly diastereo‐ and enantioselective direct aldol reaction between an hydantoin surrogate and azaarene 2‐carbaldehyde N ‐oxides is enabled by a multifunctional amine‐squaramide‐amide catalyst. The process serves to assemble carbinol‐tethered hydantoin‐azaarene conjugates featuring vicinal tertiary/quaternary carbon stereocenters (see scheme).